A Bacterial Pathogen Displaying Temperature-Enhanced Virulence of the Microalga Emiliania huxleyi - Mayers, Teaghan J.; Bramucci, Anna R.; Yakimovich, Kurt M.; Case, Rebecca J. (Frontiers in Microbiology, 2016)
Emiliania huxleyi is a globally abundant microalga that plays a significant role in biogeochemical cycles. Over the next century, sea surface temperatures are predicted to increase drastically, which will likely have significant effects on the survival and ecology of E. huxleyi. In a warming ocean, this microalga may become increasingly vulnerable to pathogens, particularly those with temperature-dependent virulence. Ruegeria is a genus of Rhodobacteraceae whose population size tracks that of E. huxleyi throughout the alga’s bloom-bust lifecycle. A representative of this genus, Ruegeria sp. R11, is known to cause bleaching disease in a red macroalga at elevated temperatures. To investigate if the pathogenicity of R11 extends to microalgae, it was co-cultured with several cell types of E. huxleyi near the alga’s optimum (18 °C), and at an elevated temperature (25 °C) known to induce virulence in R11. The algal populations were monitored using flow cytometry and pulse-amplitude modulated fluorometry. Cultures of algae without bacteria remained healthy at 18 °C, but lower cell counts in control cultures at 25 °C indicated some stress at the elevated temperature. Both the C (coccolith-bearing) and S (scale-bearing swarming) cell types of E. huxleyi experienced a rapid decline resulting in apparent death when co-cultured with R11 at 25 °C, but had no effect on N (naked) cell type at either temperature. R11 had no initial negative impact on C and S type E. huxleyi population size or health at 18 °C, but caused death in older co-cultures. This differential effect of R11 on its host at 18 °C and 25°C suggest it is a temperature-dependent opportunistic pathogen of E. huxleyi. We also detected caspase-like activity in dying C type cells co-cultured with R11, which suggests that programmed cell death plays a role in the death of E. huxleyi triggered by R11 – a mechanism induced by viruses (EhVs) and implicated in E. huxleyi bloom collapse. Given that E. huxleyi has recently been shown to have acquired resistance against EhVs at elevated temperature, bacterial pathogens with temperature-dependent virulence, such as R11, may become much more important in the ecology of E. huxleyi in a warming climate.